2017
DOI: 10.18203/2320-1770.ijrcog20170918
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical hypothyroidism in pregnancy and outcomes

Abstract: Background: Screening for subclinical hypothyroidism is essential in all pregnant women, especially in the Indian context, as Indian women have increased risk of developing iodine deficiency during pregnancy. Hence this study was undertaken to study the prevalence of subclinical hypothyroidism. Emphasis was put to know the need for universal screening and also the obstetric outcome in terms of perinatal morbidity and mortality and maternal morbidity were assessed.Methods: It was a prospective analytical study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…11 Risk of prematurity was more in SCH patient than euthyroid pregnant women but the relation was statistically insignificant. Same was seen in study done by Sannaborraiah A et al 10 In our study caesarean deliveries was significantly higher in SCH pregnant women compared to euthyroid pregnant women. This observation was statistically significant.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…11 Risk of prematurity was more in SCH patient than euthyroid pregnant women but the relation was statistically insignificant. Same was seen in study done by Sannaborraiah A et al 10 In our study caesarean deliveries was significantly higher in SCH pregnant women compared to euthyroid pregnant women. This observation was statistically significant.…”
Section: Discussionsupporting
confidence: 88%
“…Similar association had been seen in study done by Sannaboraiah A et al, compared with euthyroid pregnant women, pregnant women with SCH had a higher risk of preeclampsia. 10 The relation was statistically significant. A similar association has been found in the study done by Wilson et al, there was a statistically significant association between thyroid disorders and the risk of PIH, mild to severe pre-eclampsia.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Similar to what has been reported by Sannaboraiah et al, the incidence of premature birth was also found to be significantly higher in the SCH group as compared to euthyroid group (P=0.035). 27 Consequentially, it was seen that the incidence of LBW babies was also significantly higher in the SCH group mothers (P=0.004), a finding that also conforms to that reported by Sannaboraiah et al, and Goel et al 27,28 Limitations of the study Two thyroid function tests were performed in our study to screen pregnant subjects. Measuring antithyroid antibodies would have provided more precise data.The study population was not followed up after delivery.…”
Section: Discussionsupporting
confidence: 87%
“…There was a significant effect of maternal SCH in pregnancy on fetal distress in utero (p=0.003) [11] Männistö et al reported that maternal hypothyroidism has previously been shown to increase risk for neonatal intensive care treatment [10] . Sannaboraiah et al reported risk of NICU admission in 15% subthyroid females receiving levothyroxine whereas neonates of 27% cases with overt hypothyroidism required NICU admission [13] .…”
Section: Discussionmentioning
confidence: 99%